2020
DOI: 10.3390/ijerph17020603
|View full text |Cite
|
Sign up to set email alerts
|

Study Protocol for the Evaluation of “SuperFIT”, a Multicomponent Nutrition and Physical Activity Intervention Approach for Preschools and Families

Abstract: The promotion of healthy energy balance-related behaviours (EBRB) is already important for children at a young age. Different settings, for example childcare and home, play an important role in the EBRB of young children. Further, factors in different types of environment (e.g., physical, sociocultural and political) influence their behaviours. SuperFIT (Systems of Underprivileged Preschoolers in their home and preschool EnviRonment: Family Intervention Trial) is a comprehensive, integrated intervention approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…The present study will primarily focus on the FC. A detailed description of other elements of the SuperFIT intervention approach and research protocol can be found elsewhere [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study will primarily focus on the FC. A detailed description of other elements of the SuperFIT intervention approach and research protocol can be found elsewhere [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…SuperFIT is an intervention approach that was developed in the Netherlands and aims to promote healthy EBRBs in preschoolers [ 28 ]. SuperFIT targets both home and childcare through parents and childcare staff.…”
Section: Introductionmentioning
confidence: 99%
“…A protocol with a detailed description of the SuperFIT intervention and evaluation can be found elsewhere [32].…”
Section: Methodsmentioning
confidence: 99%
“…[24] Focusing on child's play activity level, activity type, and public interaction during play t-tests This paper finds a pattern between play and social interaction. However, it does not deal with the hidden behaviour of children [25] Focusing on factors environment influence on children their behaviours…”
Section: Literature Reviewmentioning
confidence: 99%